Population genetic structure and cladistic analysis of Trypanosoma brucei isolates - Agbo, E.C.; Clausen, Peter-Henning; Büscher, Philippe; Majiwa, Phelix A.O.; Claassen, E.; Marinus, F.W.P. (Elsevier, 2003)
Using a novel multilocus DNA marker analysis method, we studied the population genetic structure of Trypansoma brucei stocks and derived clones isolated from animal and rhodesiense sleeping sickness patients during a national sleeping sickness control program in Mukono district, Uganda. We then performed a cladistic analysis to trace relationships and evolution, using stocks and clones recovered from geographically and temporally matched hosts, including inter-strain comparisons with T. b. gambiense stocks and clones. Our results show that while there was close genetic relatedness among parasite populations from the same geographical region, micro-heterogeneities exist between different stocks. Data are presented that indicate that not every human sleeping sickness focus may be associated with a particular human-infective trypanosome strain responsible for long-term stability of the reference focus. We provide evidence of genetic sub-structuring among type 1 T. b. gambiense stocks, which has potentially important implications for molecular epidemiology of T. brucei.